Meningkatkan Hasil Belajar Matematika Siswa Kelas II MI Hidayatul Mubtadiim Menggunakan Model Pembelajaran Contextual Teaching And Learning (CTL) - Yuli Wahyuningsih (Prosiding University Research Colloquium, 2021)
The purpose of this study was to improve the Mathematics Learning Outcomes of MIHidayatul Mubtadiin Students with Contextual Teaching And Learning (CTL) LearningModels for Class II Students of MI Hidayatul Mubtadiin. This research uses ClassroomAction Research Method which consists of two cycles. The sample used in this study were7 students. The instrument used is a written test in the form of multiple choice questions.Based on the test results in cycle 1, the average value obtained is 67.8, the results still donot meet the Minimum Completeness Criteria (KKM) so that cycle II is carried out, in cycleII the average value obtained is 80.7. Contextual Teaching and Learning (CTL) learningcan improve the learning outcomes of class II students at MI Hidayatul Mubtadiin.